Comparison of Global Metabolite for Growing Pigs Fed at Metabolizable Energy Requirement for Maintenance - Liu, Hu; Chen, Yifan; Wang, Wenhui; Jiang, Zhaoning; Ma, Xi; Wang, Fenglai (Frontiers in Veterinary Science, 2022)
Though the energy requirement for maintenance is an important part of net energy system, little is known of the metabolic characteristics of maintenance energy expenditure. This study was investigated the effect of feeding level at metabolizable energy requirement for maintenance (FLM) on plasma metabolites in growing pigs. Ten barrows (22.5 ± 0.5 kg BW) were kept in metabolism crates and catheterized in the precaval vein during adaptation period. Pigs were fed a corn-soybean meal diet at 782 kJ ME/kg BW0.6·d-1 during d 1 to 8 and then were refeeding at 2,400 kJ ME/kg BW0.6·d-1 on d 9. Plasma samples of each pig were collected by catheter on the morning of d 1, 3, 5, 7, 9, and 10 respectively for metabolomics testing. Results showed that the concentration of plasma urea nitrogen decreased under FLM (p < 0.01) and increased significantly after refeeding (p < 0.01). The concentration of total cholesterol, high-density lipoprotein, low-density lipoprotein, and albumin in plasma were decreased significantly after refeeding (p < 0.01). Eleven identified compounds were up-regulated and six ones were down-regulated under FLM. In conclusion, the energy metabolism of growing pigs was relatively stable during d 4 to d 8 fed at FLM.